KRAS and BRAF mutations in Iranian colorectal cancer patients: A systematic review and meta-analysis - Abolfazl Yari; Asiyeh Afzali; Mostafa Aalipour; Mehran Nakheai; Mohammad Javad Zahedi (Babol University of Medical Sciences, 2020)
Background: Mutations in the EGFR signaling pathway play an important role in the development of colorectal cancer (CRC). Mutations in these genes, like KRAS and BRAF, affect the treatment strategies and associated with poor prognosis and relative resistance to anti-EGFR therapies. Our aim was to conduct a systematic and meta-analysis on all studies that have been conducted on the prevalence of these gene mutations in Iranian CRC patients. Methods: Four science citation index databases (MEDLINE, EMBASE, Web of Science and Cochrane library) and local databases were searched up to March 2018 with related keywords. Two reviewers independently screened and extracted the data. Quality of all included studies was assessed using an adapted checklist from STROBE. A random-effect model was used to calculate the total prevalence of KRAS and BRAF mutations in CRC subjects by the event rate (ER). Meta-regression was utilized to explore heterogeneity causes. Results: In total, from 573 records, 23 eligible studies (2662 patients) were included for data extraction and analysis. In 18 of 23 included studies, the prevalence of KRAS mutations was 33.9% (95% CI=30.1-37.9) with I2=65.17 (p<0.001). The occurrence of KRAS mutations in codon 12 and 13 was 76.9% (95% CI = 70.4-82.3%) with I2=84.88 (p<0.001) and 23.5% (95% CI=17.9-30.3) with I2=85.85 (p<0.001), respectively. In 9 of 23 studies, the BRAF mutation rate was 3.2% (95% CI=0.003-13.6) with I2=88.61 (p<0.001). Conclusion: The prevalence of these mutations in CRC patients shows a significant difference in the different regions of Iran, which is probably due to environmental and racial factors.